A flexible and conductive metallic paper-based current collector with energy storage capability in supercapacitor electrodes. Issue 22 (3rd May 2019) - Li, Yaoyin; Wang, Qiyuan; Wang, Yong; Bai, Mingjun; Shao, Jian; Ji, Hongjun; Feng, Huanhuan; Zhang, Jiaheng; Ma, Xing; Zhao, Weiwei
Abstract : Flexible and conductive paper-based current collectors are fabricated by directly depositing metallic Ni layer composed of spiny Ni nanospheres on the surface of paper via electroless deposition and exhibit excellent mechanical properties and electrochemical performance. Abstract : The development of flexible current collectors as an indispensable component in energy storage devices has been in strong demand for the ever-growing market of flexible and wearable electronics. Herein, flexible and conductive paper-based current collectors are fabricated by directly depositing a metallic Ni layer composed of spiny Ni nanospheres of 400 nm diameter on the surface of filter paper via electroless deposition. The metallic paper shows excellent electric and mechanical properties: the sheet resistance is 2.7 Ω cm −2 ( R 0 = 0.8 Ω cm −2 ) after 5000 bending cycles and the mass density is only 0.35 g cm −3 . MnO2 is selected as an electrode active material to explore the role of flexible and conductive paper-based current collectors in supercapacitors. Electrochemical results reveal that the largest areal specific capacitance is 1095 mF cm −2 at 1 mA cm −2 and the excellent electrochemical performance can be attributed to the hierarchical porous fibre structure of paper and the lower contact resistance between the active material and the current collector. Note that the approach can be applied to an enlarged size of metallic conductive paper or textile, presenting a simple and feasible method to fabricate flexible current collectors in a large scale.